Customer Focus and Organisational Culture Increasing Work Life Balance Moderated by Supportive Management - Sigit Dani Nugroho; Agus Riyanto; Parlagutan Silitonga (Annals of Human Resource Management Research, 2026)
Purpose: Demanding work-life balance is a human right; therefore, this study aimed to design evidence-based interventions to improve work-life balance. Research Methodology: This study was conducted from December 2024 to March 2025, involving 220 respondents who were employees of an industrial company in the Cikarang, Karawang, and Jakarta regions. The instrument was tested for validity and reliability among 30 respondents prior to the actual survey. Data were analyzed by PLS-SEM using SmartPLS software version 3.0. Results: The organizational culture and supportive management in promoting work-life balance also suggest that their interaction effects are limited in this context. These findings offer theoretical and practical implications for developing comprehensive HR strategies to promote employee well-being. Conclusions: This study provides empirical evidence that organizational culture and supportive management play significant and independent roles in shaping employees' perceptions of work-life balance (WLB). Among the examined variables, supportive management was the most influential factor, followed closely by organizational culture. Limitations: The respondents were permanent staff, excluding non-permanent staff on contract. Limitations: The respondents were permanent staff, excluding non-permanent employees on a contract basis, even though their WLB matters. Contributions: This study contributes to the body of knowledge on managing work-life balance through cultural engagement and supportive management.